2017
DOI: 10.3389/fpsyg.2017.01890
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship between Job Demands and Employees’ Counterproductive Work Behaviors: The Mediating Effect of Psychological Detachment and Job Anxiety

Abstract: This study aims to explore the relation between job demands and counterproductive work behaviors (CWBs). A cross-sectional sample of 439 coal miners completed a self-report questionnaire that assessed their job demands, psychological detachment, job anxiety, and CWBs in a Chinese context. The conceptual model, based on the stressor-detachment model, was examined using structural equation modeling. The results suggest that psychological detachment mediates not only the relation between job demands and job anxie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
37
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 49 publications
(41 citation statements)
references
References 120 publications
3
37
0
1
Order By: Relevance
“…We applied the bootstrapping procedure ( Preacher and Hayes, 2004 ) with 1,000 subsamples to estimate the direct and indirect effects in our conceptual model. Bootstrapping is more powerful than the method of Baron and Kenny (1986) to check the mediation effect, as it is unnecessary to assume that samples are of normal distribution and it also can obtain a more confident estimation of the indirect effect ( Mackinnon et al, 2002 ; Chun et al, 2014 ; Chen et al, 2017 ). If the 95% confidence interval (CI) does not contain zero, then the direct and indirect effects are significant.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…We applied the bootstrapping procedure ( Preacher and Hayes, 2004 ) with 1,000 subsamples to estimate the direct and indirect effects in our conceptual model. Bootstrapping is more powerful than the method of Baron and Kenny (1986) to check the mediation effect, as it is unnecessary to assume that samples are of normal distribution and it also can obtain a more confident estimation of the indirect effect ( Mackinnon et al, 2002 ; Chun et al, 2014 ; Chen et al, 2017 ). If the 95% confidence interval (CI) does not contain zero, then the direct and indirect effects are significant.…”
Section: Resultsmentioning
confidence: 99%
“…As for organizations, supervisors should be discouraged from assigning tasks to employees during non-work time unless in the case of emergencies. Furthermore, organizations should provide some training and guidance to employees with insufficient psychological detachment, such as in setting priorities, time-management skills, and job skills, to ensure they finish tasks on time and avoid ruminating on work-related issues in off-hours ( Sonnentag et al, 2014 ; Chen et al, 2017 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Voice behavior is beneficial for highlighting individual contributions (Kwon et al, 2016), improving team processes (LeClair-Smith et al, 2016), avoiding potential crises (Chamberlin et al, 2017), and enhancing organization performance (Hilverda et al, 2018). Job stressors have been regarded as one of the most critical inhibitors of voice behavior, since job stressors are widespread and unavoidable, more importantly; research has found that job stressors are negatively related to major work-related outcomes (Chen et al, 2017). Although literature has focused on the relationships between job stressors and voice behaviors (Hu et al, 2018), further research on psychological mechanisms and empirical evidence is still needed (Chen et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…There is overwhelming research evidence that an employee's negative mental state affects their work behaviour (Chen et al 2017;Rajgopal 2010;Sahler and Dubois 2009). Given the fact that caregiver work behaviours have frequently been called into question in the Ghanaian residential child care contexts (Anas 2010(Anas , 2015FrimpongManso 2016;Smith-Asante 2014) the need for debate and reconsideration of the current states of the organizational structures could not be more urgent.…”
Section: Organizational Formmentioning
confidence: 99%